PENGARUH MEDIA SOSIAL, KUALITAS PRODUK, DAN HARGA TERHADAP MINAT BELI SEPEDA LISTRIK MEREK U-WINFLY DI KUDUS - Wardani, Rina Umi; Aqliya, Jauharotun Sholha; Rasyida, Ana Mar’atur; Andni, Riyan; Candra, Eki (Universitas Dharmawangsa, 2025)
Abstract This study examines the influence of social media, product quality, and price on the purchase intention of U-WINFLY electric bicycles in Kudus. This study uses a quantitative approach, utilizing normality tests to ensure that the data distribution is suitable for analysis. The results show that all social media, product quality, and price variables are normally distributed, with skewness and kurtosis values in the acceptable range, confirming the reliability of the data for further analysis. This study consisted of 112 people, who were selected beyond the purposive sampling system by analyzing the data using the Econometric Views 8 (E-views 8) program. The literature review highlights the importance of social media as a marketing tool, emphasizing its efficiency in promoting products and maintaining customer relationships at low cost compared to traditional sales methods. In addition, it discusses the role of product quality in shaping consumer trust and purchasing behavior, showing that consumer perceptions of quality directly affect their purchasing decisions.